Programa educativo de organizadores gráficos para mejorar la comprensión de textos escritos en estudiantes de tercer grado de secundaria en la institución educativa José Olaya Balandra en el distrito de San Juan Bautista 2023 - Miranda Lopez, Betsy Danitza (2024)
The aim of this research was to enhance the comprehension of written English texts by implementing a graphic organizer educational program for third-grade secondary students at the José Olaya Balandra school in San Juan Bautista district in 2023.The research type was evaluative with a field study, contemporary transectional, univariable and quasi-experimental designs. The study population was made of 41 students, divided in two groups, in which 20 were part of the experimental group and 21 students were part of the control group. A validated and reliable comprehension test was used to obtain data. The results show that the experimental group obtained a significantly higher average than the control group (15,627 > 8,883) after the induction of the graphic organizer educational program. Likewise, this difference can be seen in the dimensions, getting information (16,667>12,422), inferencing and interpreting (15,083>6,884), and evaluation of text content, context and format (14,778>6,232). It is concluded that graphic organizers significantly improve students' text comprehension, reaching the expected achievement with a mean of 15.627 and a p-value = 000.0.